2018
DOI: 10.11152/mu-1161
|View full text |Cite
|
Sign up to set email alerts
|

Value of Shear Wave Elastography for differentiating benign and malignant renal lesions

Abstract: Aims: To investigate the diagnostic accuracy of shear-wave elastography (SWE) for assessing malignant and benign kidneymasses.Materials and methods: Forty patients with solid renal masses underwent US elastographic evaluation. SWE values of the lesions and adjacent cortical renal parenchyma and SWER were detected prospectively. Malignant tumors were recorded as group 1 and benign tumors were recorded as group 2.Results: The highest elasticity values were 27.27±25.66 kPa for group 1 and 16.13±8.89 kPa for group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Two studies described the ability of 2D SWE to differentiate RCC and AML, with contradicting results on which of the two entities has the higher stiffness. The main reason for this disparity seems to be the size of the masses included in the study, as one research included only tumors < 4 cm with a mean of 2.96 ± 0.89 cm, while the other enlisted patients indiscriminately, with a mean diameter of 5.23 ± 3.42 cm [ 18 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies described the ability of 2D SWE to differentiate RCC and AML, with contradicting results on which of the two entities has the higher stiffness. The main reason for this disparity seems to be the size of the masses included in the study, as one research included only tumors < 4 cm with a mean of 2.96 ± 0.89 cm, while the other enlisted patients indiscriminately, with a mean diameter of 5.23 ± 3.42 cm [ 18 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Less than ten studies have been published which have tried to differentiate benign from malignant renal mass based on elasticity. Amongst these, several have done strain elastography[ 23 , 24 ] and several shear wave elastography[ 22 , 25 ]. No standardized values have been obtained yet.…”
Section: Advanced Imaging Techniquesmentioning
confidence: 99%
“…One of the studies postulates elasticity values in the range of 4.5-4.7 ± 1.5-1.7 kPa of the normal renal cortex[ 22 ]. A study by Aydin et al [ 25 ] evaluated 40 renal masses and found the highest elasticity value in the malignant and benign groups to be 27.27 ± 25.66 kPa and 16.13 ± 8.89 kPa, respectively. However, more studies with a larger number of patients are required to authenticate these findings and establish a nomogram and cut-off for elasticity values of benign and malignant lesions.…”
Section: Advanced Imaging Techniquesmentioning
confidence: 99%
“…It quantitatively assesses tissue rigidity through Young's modulus (YM), providing complementary information about the focal lesions. 14,15 The application value of SWE in breast cancer, thyroid nodules, and fibrosis of chronic liver diseases has been confirmed. Recently, SWE has attracted wide attention in the diagnosis of renal injury with emphasis on the degree of kidney stiffness.…”
mentioning
confidence: 91%
“…Shear wave elastography (SWE) is a non‐invasive method developed in recent years to evaluate the elasticity of living tissue. It quantitatively assesses tissue rigidity through Young's modulus (YM), providing complementary information about the focal lesions 14,15 . The application value of SWE in breast cancer, thyroid nodules, and fibrosis of chronic liver diseases has been confirmed.…”
Section: Introductionmentioning
confidence: 99%